The effect of waste tire granules on the properties of polyethylene terephthalate thermoplastic - Ong Huei Ruey; Iskandar Wan Mohd Eqhwan; Khan Maksudur Rahman; Ong Thai Kiat; Hong Chi Shein (E3S Web of Conferences)
The utilization of waste tire granules (WTG) as a reinforcing agent in polyethylene terephthalate (PET) offers a sustainable approach to enhancing thermoplastic composites. PET is known for its recyclability, while WTG provides a solution for waste tire management. This study examines the effect of WTG content and particle size on PET/WTG composites. Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR) were used to analyze the composites' morphology and chemical composition. Mechanical tests evaluated elongation and impact performance with WTG incorporation. SEM showed a compatible morphology between the PET matrix and WTG. FTIR spectra displayed characteristic vibrations of polyisoprene from WTG and PETspecific functional groups. The inclusion of WTG significantly improved mechanical properties that leads to enhanced elongation at break (EB) and increased ductility. Impact strength also improved notably at 10% WTG. These findings demonstrate the potential of WTG as a filler to enhance PET mechanical properties and contribute to sustainable waste management as well as the development of value-added products from recycled materials.